An interview with Naomi L. Shin - Naomi Shin (Isogloss, 2020)
Naomi L. Shin is an Associate Professor of Linguistics and Hispanic Linguistics at the University of New Mexico. Her primary interests include child language acquisition, bilingualism, language contact, and sociolinguistics. Her research focuses on patterns of morphosyntactic variation, examining how these patterns are acquired during childhood and how they change in situations of language contact. Her articles have appeared in journals such as Journal of Child Language, Cognitive Linguistics, International Journal of Bilingualism, Language Acquisition, Language Variation and Change, Language in Society, Foreign Language Annals, Spanish in Context, Studies in Hispanic and Lusophone Linguistics, and International Journal of the Sociology of Language. She is the co-author of Gramática Española: Variación Social, which explores grammar in a way that emphasizes the social underpinnings of language.